Career maturity and career decision-making self-efficacy as predictors of career adaptability among students in foundation program, Universiti Putra Malaysia - Abdul Rahim, Nor Syazila; Wan Jaafar, Wan Marzuki; Mohamad Arsad, Nurazidawati (UiTM Press, 2021)
This study aims to examine the key predictors between career maturity and career decision-making self-efficacy on career adaptability among students in the Foundation Studies for the Agricultural Science programme at Universiti Putra Malaysia (UPM).A quantitative research design using a questionnaire consists of career maturity, career decision-making self-efficacy and career adaptabilities was disseminated to the respondents. Using the cluster sampling method, a total of 329 students were involved in the study. The results indicate that these variables are significantly correlated and suggest that students who are able to have more career maturity or have more self-efficacy in their careers are more susceptible to self-adaptation. Employing hierarchical multiple regression analysis, it was discovered that career competency is the best predictor of career adaptability in relation to career maturity. Meanwhile, career goal-selection and career planning are the best predictors of career adaptability in relation to career decision-making self-efficacy. This study found that developing career maturity with a focus on students’ career competency and career decision-making self-efficacy with an emphasis on career goal-selection and career planning in higher education plays an important role in enhancing their overall career adaptability and preparing them for future career success.